2021
DOI: 10.1186/s13059-021-02529-2
|View full text |Cite|
|
Sign up to set email alerts
|

The SEQC2 epigenomics quality control (EpiQC) study

Abstract: Background Cytosine modifications in DNA such as 5-methylcytosine (5mC) underlie a broad range of developmental processes, maintain cellular lineage specification, and can define or stratify types of cancer and other diseases. However, the wide variety of approaches available to interrogate these modifications has created a need for harmonized materials, methods, and rigorous benchmarking to improve genome-wide methylome sequencing applications in clinical and basic research. Here, we present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
(32 reference statements)
4
18
0
Order By: Relevance
“…To compare WGMS data generated by the UG sequencer to WGMS methods we sequenced the standard reference HG001, HG002 and HG005 cell-lines using both EM-seq 25 and Bisulfite 26 conversion methods and compared our data with the recently published Genome in a Bottle (GIAB) EpiQC data 27 . Using the UG sequencer we sequenced an average of 922 million reads per sample for each of the methods with two to five replicates (Supplementary table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To compare WGMS data generated by the UG sequencer to WGMS methods we sequenced the standard reference HG001, HG002 and HG005 cell-lines using both EM-seq 25 and Bisulfite 26 conversion methods and compared our data with the recently published Genome in a Bottle (GIAB) EpiQC data 27 . Using the UG sequencer we sequenced an average of 922 million reads per sample for each of the methods with two to five replicates (Supplementary table 1).…”
Section: Resultsmentioning
confidence: 99%
“…To gain insight on the tissue composition of these samples we applied a computational method for methylation-based cell type deconvolution 27 (methods; Supplementary Fig 3c). This analysis revealed that three of the adenocarcinoma samples had a negligible colon fraction and one of them contained a high fraction of lung cells.…”
Section: And Supplementary Fig 3b)mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, most 5mCs occur at CpG sites, which are associated with cancer 2 , embryonic development 3 and aging 4 . Bisulfite sequencing (BS-seq) is now the most widely used methodology for profiling 5mC methylation 5,6 . In a bisulfite treated genomic DNA, unmethylated cytosines are converted to uracils, while methylated cytosines are unchanged 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified the following errors: Jonathan Foox, Jessica Nordlund, Claudia Lalancette, Ting Gong, Michelle Lacey and Samantha Lent are co-first authors. Affiliation 21 was incorrectly published.…”
mentioning
confidence: 99%